Influência da pré-molhagem nas propriedades de concretos produzidos com agregado reciclado de concreto - Padovan, Rafaela Gava (Universidade do Vale do Rio dos Sinos, 2013)
Recycled aggregates have high water absorption properties due to its high porosity. It changes the water content of the mixtures, and has implications on the microstructural properties of cement-based materials as those who uses recycled aggregate; however, little is known about these materials. This research has the objective of determining the influence of aggregate pre-wetting in new concrete made with recycled coarse aggregate concrete (RCAC) replacing natural aggregate. The substitution ratio of natural coarse aggregate (NCA) in relation to RCAC was 50% relative to the volume of the concrete. Prior to employing RCAC, it was pre-wetted with pre-wetting levels of 40, 60, 80 and 100% of the total water absorption of the residue. Water to cement ratios were initially determined to be 0.45, 0.55 and 0.65. The slump was set at 100 ± 20 mm, performing a compensation on the water content of the mixture required to get this slump. In a second group, the smallest amount of water used in the concrete’s production without additive was set with saturation levels of 40, 60 and 80%, using a superplasticizer instead of water to achieve the required slump. The recycled concrete produced was found to influence the pre-wetting RCAC on the properties of fresh concrete, through determination of consistency over time, compressive strength and durability and water absorption by capillarity. Mortar samples were obtained from the extraction of recycled concrete. These samples were analyzed for porosity. The results indicate that the workability and the compressive strength of concretes with AGRC are little influenced by the amount of pre-wetting, while the water permeability and the void content of the mixture existing in the mortar suffer significant influence: in the concrete with no additive AGRC there are small variations in porosity and permeability, and in the amount of pre-wetting results in 80% less porous concrete. However, in concrete with AGRC and superplasticizer, the lowest level of pre-wetting tested (40%) proves the best option, because the mixing water is absorbed by the empty pores of recycled aggregate, which reduces the porosity of the mortar, and consequently the capillarity of hard concrete.
Influence of pre-wetting on properties of concrete produced with recycled concrete aggregate
Keywords: Agregado reciclado de concreto; Pré -molhagem; Trabalhabilidade; Resistência à compressão; Permeabilidade; Recycled concrete aggregate; Pre-wetting; Workability; Compressive strength; Permeability; ACCNPQ::Engenharias::Engenharia Civil